The Scope and Conditions of the European Union's Innovation Policy - Andrzej Wiatrak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This article aims to present the nature and the many directions of support for innovation processes in the EU on the one hand and to indicate the orientations of this support that could be used by Poland, including by agribusiness, on the other. The article covers the following: the nature, objectives and tools of innovation policy implementation, evolution of the European Union’s innovation policy, characteristics of EU innovation policy measures after 2010, and characteristics of EU innovation policy measures in agribusiness after 2010. It is clear from the discussion herein that innovative actions and their support in the EU encompass not only technological but also social and environmental issues, with innovation and its support being the cornerstones of various policies, hence it is important to address them systemically. In particular, tools for implementing innovation policy and innovation partnerships at various levels play a role in this respect. The article is based on the related literature as well as documents and materials concerning the EU’s innovation policy.